Предмет: Алгебра,
автор: dmitrievkosta685
a(8a² – 4a) – a² (5a - 4)
(6a – 8ab) + 4a(2b - 3)
8(ab - c) – (8ab + 3c)
4c(-3a + b) – 2c(2b – 3a)
-4m(5m² + 6) – 5(m – 4m³)
даю 20 баллов
Ответы
Автор ответа:
2
1) a(8a² - 4a) - a²(5a - 4) = 8a³ - 4a² - 5a³ + 4a² = 3a³
2) (6a - 8ab) + 4a(2b - 3) = 6a - 8ab + 8ab - 12a = - 6a
3) 8(ab - c) - (8ab + 3c) = 8ab - 8c - 8ab - 3c = - 11c
4) 4c(- 3a + b) - 2c(2b - 3a) = - 12ac + 4bc - 4bc + 6ac = - 6ac
5) - 4m(5m² + 6) - 5(m - 4 m³) = - 20m³ - 24m - 5m + 20m³ = - 29m
Похожие вопросы
Предмет: Русский язык,
автор: esayll11
Предмет: Русский язык,
автор: kirill851
Предмет: Другие предметы,
автор: ksenazueva
Предмет: История,
автор: teteevaa031
Предмет: Обществознание,
автор: Fortunée